2014
DOI: 10.1002/dta.1616
|View full text |Cite
|
Sign up to set email alerts
|

The syntheses, characterization and in vitro metabolism of nitracaine, methoxypiperamide and mephtetramine

Abstract: Three legal highs; nitracaine (3-(diethylamino)-2,2-dimethylpropyl 4-nitrobenzoate), methoxypiperamide (MEOP, (4-methoxyphenyl)(4-methylpiperazin-1-yl)methanone) and mephtetramine (MTTA, 2-((methylamino)methyl)-3,4-dihydronaphthalen-1(2H)-one) appeared in 2013 as new psychoactive substances (NPS) on Internet websites selling 'research chemicals'. These compounds were synthesized and analyzed via our synthesize, analyze, and metabolize (SAM) protocol. Nitracaine was synthesized by the transesterification of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The synthesis and characterization of nitracaine (3‐(diethylamino)‐2,2‐dimethylpropyl 4‐nitrobenzoate), methoxypiperamide (4‐methoxyphenyl) (4‐methylpiperazin‐1‐yl)methanone) and mephtetramine (2‐((methylamino)methyl)‐3,4‐dihydronaphthalen‐1(2 H )‐one) was described by Power et al who encountered these substances as ‘research chemicals’ from online vendors in 2013. The authors extended the work to the incubation with pooled human liver microsomes to assess their transformation by LC‐MS . The presence of nitracaine was also confirmed in a test purchase.…”
Section: The Need For Synthetic and Analytical Chemistrymentioning
confidence: 99%
“…The synthesis and characterization of nitracaine (3‐(diethylamino)‐2,2‐dimethylpropyl 4‐nitrobenzoate), methoxypiperamide (4‐methoxyphenyl) (4‐methylpiperazin‐1‐yl)methanone) and mephtetramine (2‐((methylamino)methyl)‐3,4‐dihydronaphthalen‐1(2 H )‐one) was described by Power et al who encountered these substances as ‘research chemicals’ from online vendors in 2013. The authors extended the work to the incubation with pooled human liver microsomes to assess their transformation by LC‐MS . The presence of nitracaine was also confirmed in a test purchase.…”
Section: The Need For Synthetic and Analytical Chemistrymentioning
confidence: 99%
“…Alex and coworkers designed naphthalenyl dihydroimidazoles with the inspiration of napamezole‐based hybrid library, which suggested that the potential antidepressants can display combined α 2 ‐adrenoceptor antagonist and monoamine uptake inhibitor properties . Mephtetramine represent yet another generation of new psychoactive substance . Liu et al., discovered a series of novel naphthalenyl pyrimidinones as potent HIV‐1 inhibitors (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Other isobaric compounds were taken in to account for the raw formula C 12 H 13 NO. Power et al 6 postulated the formation of a di‐hydro isoxazole derivative, obtained by N ‐oxidation, cyclization, and dehydration. This hypothesis was discarded because of the presence of the fragment ion at m / z 170.0965, not compatible with the structure proposed.…”
Section: Resultsmentioning
confidence: 99%